Salvation and Discipleship Continuum in Johannine Literature Toward an Evaluation of the Faith Alone Doctrine. - James, Sujaya (Lewiston : The Edwin Mellen Press, 2014)
An honest and significant response to the Faith Alone or Free Grace Movement. In this work Dr. Sujaya James tackles the inherent link between salvation/assurance and discipleship in the writings of the Apostle John to demonstrate that Faith Alone teaching is inconsistent with John's presentation of salvation and discipleship continuum.
Print version record.
Keywords: Bible. Epistles of John -- Criticism, interpretation, etc; Bible. John -- Criticism, interpretation, etc; Salvation -- Biblical teaching; Salvation -- Christianity; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Salvation -- Biblical teaching; Salvation -- Christianity; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books